A novel design and development of persistence layer for heterogeneous synchronous replication in data grid - Beg, A. H.; Noraziah, Abu Yazid; Abdalla, Ahmed N. (Academic Journals, 2011)
Data grid provided a way to solve the problems of large-scale data management. Data-intensive applications such as high-energy physics and Bioinformatics required both computational and data grid features. Replication is a process to achieved efficient and fault-tolerant access in the data grid. Usually, data replication schemes maintain an entire replica in every site where a file is replicated. It provided an important role in this involving world of the distributed database system. Replication technology should be efficient, thereby facilitates the maintenance costing. Most traditional replication technique is cost effective and also not considers the heterogeneous system. This paper presented a new model of persistence layer for synchronous replication and implemented based on multi-threading in heterogeneous environment. The main objective of this model is to make the persistence layer adaptive and make the replication process reliable and faster than other existing replication processes concerning cost minimization. In the proposed replication technique, the replication servers are operating system independent and the entire replication process is not inter dependent nevertheless on the main server. Adding a new replication server is easier than other processes. The technique also introduces the modification of replication servers without making impairment to the entire process. The performance of the proposed technique has been compared with SQL Server in terms of transactional inserts and synchronization time. The result shows that PLSR performs outstandingly than SQL server for transactional insert and synchronization in compare to time (seconds).